Children's mathematics web sites an analysis - Alegre, Valerie Faye E.; Reside, Marie Desiree H. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Librarians nowadays are faced with the challenges brought upon by the Internet, a new source of information that is dynamic, interrelated, uncontrolled, expanding and instantaneously accessible (Schacter, Chung and Dorr,1998). With more and more children using the World Wide Web as a learning tool, it is essential to critically analyze the web sites populating the Information Superhighway.
The population used for the study was the nineteen web sites featured in the mathematics category in http://KidSites.com.Two evaluation tools were utilized for the completion of this paper. First was the checklist based on the standards developed by the Association for the Library Service to Children (ALSC), Children and Technology Committee. This was used to measure if a web site is worthwhile place to spend time. The second tool was the Haughland/Gerzog Developmental Scale for Web Sites. The scale gauged the developmental appropriateness of an Internet site. This ensures that children can learn through active exploration and trial and error, which can be provided by open-ended software. Such materials are said to be developmentally appropriate.
The evaluation was done by 6 respondents comprised of 4 elementary teachers and 2 high school teachers from the Mathematics Department of the University of the Philippines Integrated School. The 19 web sites were divided among the respondents. After a month of evaluation, the percentages and scores for the checklist and the developmental scale were computed by the researcher. Results were tabulated, analyzed and presented using the Microsoft Excel with its Analysis TollPak activated to generate frequency tables, histograms and cumulative graphs.
All 19 web sites complied with more than 50 percent of the criteria prepared by the ALSC. However, only five of them passed the Haughland/Gerzog Web Scale. Fifteen out of the 34 characteristics listed in the ALSC criteria were reflected by all web sites that were both worthwhile and developmentally appropriate.
Further research as regards the relation ship between the two evaluation tools used in this paper was recommended. Moreover, it was suggested to gather all existing evaluation tools for web sites for thorough examination, comparison and analysis. This procedure may spearhead the building of a potential standard that can be used to assess Internet sites in the future.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman Diliman
Keywords: University of the Philippines Integrated School; Children's web sites; Mathematics teachers -- Philippines -- Quezon City